2018
DOI: 10.1051/e3sconf/20184002056
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of low-angle dune morphodynamics

Abstract: Dunes commonly dominate the bed of sandy rivers and they are of central importance in predicting flow resistance and water levels. In the present study, we show that by using light-weight polystyrene particles as substrate in a laboratory setting, promising morphodynamic similarity is obtained between dunes in shallow flow (flume) and deep flow (field) conditions. In particular, results from our flume experiments show that dune lee-side angles, which are crucial in turbulence production and energy dissipation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Based on our results and previous research (e.g. Best and Kostaschuk, 2002;Bradley et al, 2013;Kwoll et al, 2016; Naqshband et al, 2018;Kostaschuk and Villard, 1996), properties of each dune category can be identified (Fig. 9).…”
Section: Low- Intermediate-and High-angle Dunessupporting
confidence: 57%
“…Based on our results and previous research (e.g. Best and Kostaschuk, 2002;Bradley et al, 2013;Kwoll et al, 2016; Naqshband et al, 2018;Kostaschuk and Villard, 1996), properties of each dune category can be identified (Fig. 9).…”
Section: Low- Intermediate-and High-angle Dunessupporting
confidence: 57%
“…One should be sure though to non-dimensionalise space and time with typical length and time scales to tune the weighting of the nearest neighbours in this three-dimensional LOESS approach. Although a numerical implementation is already available for an unlimited amount of dimensions, this has not been applied yet [Vermeulen, 2016].…”
Section: Future Research Directions 621 Bed Level Monitoringmentioning
confidence: 99%